Gravida 7 para 4 abortus 2 (G7P4A2) for multiple repeat caesarean section: general or neuroaxial anesthesia - Dewi Yulianti Bisri; Tatang Bisri (ACTA Medical Health Sciences, 2023)
A caesarean section (CS) is a surgical procedure that has several risks, such as uterine rupture, infection, bleeding, thrombosis, and damage to the bladder, ureters, or intestines. Compared to primary CS, multiple repeat caesarean sections (MRCS) are associated with additional risks, including placenta previa, abnormal placental invasion, difficulty in surgical dissection, longer surgeries, and greater amounts of bleeding. A woman, age 40 years, G7P4A2, gravida aterm, weight 64.4 kg, height 150 cm, Mallampati score 1, open mouth >3 cm, thyromental distance > 3 fingers, neck circumference 33 cm, former caesarean section 4 times, would have her caesarean section and sterilization at Melinda Woman Hospital Bandung-Indonesia. A caesarean section was performed under general anesthesia, induction with propofol, atracurium, and sevoflurane, and maintenance anesthesia with N2O/O2-sevoflurane. Induction-delivery time: 16 minutes, uterine incision 50 seconds, baby born with 1-minute Apgar score was 9 and 5-minute Apgar score was 10. Analgetic fentanyl is given after birth at a dose of 1.5 mcg/kgBw intravenously. There were no caesarean-section complications. Postoperatively, the patient was treated in the wards. Due to concerns about heavy bleeding, which would require massive transfusions, anesthesia was performed under general anesthesia due to the fact that massive transfusions make patient uncomfortable because of various complications of massive transfusion DOI : 10.35990/amhs.v2n1.p38-45 REFERENCE Cook JR, Jarvis S, Knight M, Dhanjal MK. Multiple repeat caesarean section in the UK: incidence and consequences to mother and child. A national, prospective, cohort study. BJOG. 2013;120(1):85–91. doi:10.1111/1471-0528.12010. [PubMed][Google Scholar] Rashid M, Rashid RS. Higher order repeat caesarean sections: how safe are five or more? BJOG. 2004;111(10):1090–1094. doi:10.1111/j.1471-0528.2004.00244.x. [PubMed][Google Scholar] Biler A, Ekin A, Ozcan A, Inan AH, Vural T, Toz E. Is it safe to have multiple repeat caesarean sections? A high volume tertiary care center experience. Pak J Med Sci. 2017 Sep-Oct;33(5):1074–1079. Sobande A, Eskandar M. Multiple repeat caesarean sections: complications and outcomes. J Obstet Gynaecol Can. 2006;28(3):193–197. doi:10.1016/S1701-2163(16)32105-3. [PubMed][Google Scholar] Wu S, Kocherginsky M, Hibbard JU. Abnormal placentation: twenty-year analysis. Am J Obstet Gynecol. 2005;192(5):1458–1461. doi:10.1016/j.ajog.2004.12.074. [PubMed][Google Scholar] Dewi Yulianti Bisri, et al. Juntunen K, Makarainen L, Kirkinen P. Outcome after a high number (4-10) of repeated caesarean sections. BJOG. 2004;11(6):561–563. doi:10.1111/j.1471-0528.2004.00154.x. [PubMed][Google Scholar] Clark SL, Koonings PP, Phelan JP. Placenta previa/accreta and prior caesarean section. Obstet Gynecol. 1985;66(1):89–92. [PubMed][Google Scholar] Silver RM, Barbour KD. Placenta accrete spectrum: accrete, increta, and percreta. Obstet Gynecol Clin North Am. 2015;42(2):381–402. doi:10.1016/j.ogc.2015.01.014. [PubMed][Google Scholar] Seidman DS, Paz I, Nadu A, Dollberg S, Stevenson DK, Gale R, et al. Are multiple caesarean sections safe? Eur J Obstet Gynecol Reprod Biol. 1994;57(1):7–12. [PubMed][Google Scholar] Afolabi BB, Lesi FEA, Merah NA. Regional versus general anesthesia for caesarean section. Cochrane Database Syst Rev. 2012. Christiana M, Bisri T. The effect of general anesthesia compared to spinal anesthesia for caesarean section on neonatal APGAR score. Anesthesia & Critical Care. 2015;33(2):99-106. Bisri T, Rochmah EN, Kurniawan A, Stela A. The comparison between spinal anesthesia bupivacaine and sevoflurane anesthesia for caesarean section on Apgar score. AMHS. 2023;1(3):128-36. Bisri DY, Bisri T. Experience in elective caesarean section under general anesthesia in more than 5000 patients at Melinda Women Hospital Bandung-Indonesia. OAMJMS. 2023. Shah RK, Ansari S, Musthaq R, Shah P, Shrestha R, Deep JG. Primary caesarean section among multiparous pregnant women visiting a tertiary care centre: a descriptive cross-sectional study. J Nepal Med Assoc. 2022;60(254):848-52. Aryasa T, Sari AR, Marwoto. Aliran darah uteroplacenta. In: Bisri DY, Uyun Y, Soewondo BS, Wahjoeningsih S, Bisri T, eds. Obstetri Anesthesia & Critical Care. Subkomisi Pendidikan Subspesialis Obsteri KATI, September 2021, 55. Alchalabi HA, Amarin ZO, Badria LF, Zayed FF. Does the number of previous caesarean deliveries affect maternal outcome and complication rates? Mediterr Health J. 2007 May-Jun;13(3):544-50. Gasim T, Al Jama FE, Rahman MS, Rahman J. Multiple repeat caesarean sections: operative difficulties, maternal complications and outcome. J Reprod Med. 2013;58(7-8):312–318. [PubMed][Google Scholar] Rouse DJ, MacPherson C, Landon M, Varner MW, Leveno KJ, Moawad AH, et al. Blood transfusion and caesarean delivery. Obstet Gynecol. 2006;108(4):891–897. doi:10.1097/01.AOG.0000236547.35234.8c. [PubMed][Google Scholar] Silver RM, Landon MB, Rouse DJ, Leveno KJ, Spong CY, Thom EA, et al. Maternal morbidity associated with multiple repeat caesarean deliveries. Obstet Gynecol. 2006;107(6):1226–1232. doi:10.1097/01.AOG.0000236547.35234.8c. [PubMed][Google Scholar]